Life Stories of Women: Terminated Parental Rights - Volkova, Olga A.; Naberushkina, Elmira K.; Besschetnova, Oksana V.; Mozgovaya, Elena I.; Svishcheva, Irina K. (Journal of History Culture and Art Research, 2018)
The article presents the results of the analysis of women’s life stories whose parental rights are terminated. The applied sociological research is conducted in three Russian regions: Belgorod, Saratov regions and the Trans-Baikal Territory in 2017. The main method for the collection of primary data is the depth interview (n = 15). The study evaluates the analysis of an individual case and the reconstruction of frames which are based on the observed practices of destructive maternity, and help to identify two main strategies of women’s behavior referring to the role of “mother”. The first strategy is related to the place of motherhood in the self-identity system that means the stronger the awareness of a woman herself as a “parent”, the more likely the child will be returned home. One of the most stimulating factors increasing the maternal awareness is the influence of woman’s immediate environment, including members of extended family or a new spouse. The second strategy demonstrates conscious changes in women’s life trajectories regarding voluntary renunciation from the role of parent under difficult circumstances. The subjective paradigms of the second strategy, based on the self-excuse (the child will be better in an orphanage or in a foster family) and are accompanied by the identity crisis and the deep degradation of woman’s personality.